Influence of meteorological conditions on herpes zoster occurrence: a retrospective cohort study - Ochal, Michał; Glińska Lewczuk, Katarzyna; Dragańska, Ewa; Cymes, Iwona; Romaszko, Jerzy (Frontiers in Medicine, 2025)
IntroductionHerpes zoster is caused by the reactivation of the varicella zoster virus, typically affecting older adults and immunocompromised individuals. Although various studies have examined potential triggers, the influence of meteorological conditions on herpes zoster reporting remains unclear. We aimed to investigate whether meteorological and biometeorological factors, including the Universal Thermal Climate Index (UTCI) and the H index (air cooling power), have an effect on herpes zoster occurrence.MethodologyWe performed a retrospective analysis of medical records for herpes zoster cases (ICD-10 code B02) from 2009 to 2023 at two medical facilities in northeastern Poland. Local meteorological data were obtained from regional stations. Statistical analyses accounted for patient age, seasonality, and thermal conditions (as measured by UTCI).Results and discussionNo seasonal pattern in herpes zoster reporting was observed, and there were no statistically significant correlations between basic meteorological variables (ambient temperature, relative humidity, wind speed, etc.) and the number of cases. However, results showed that under strong heat stress conditions (UTCI class 8), the risk of herpes zoster was approximately 20–25% higher compared to thermally neutral days.ConclusionHerpes zoster occurrence does not exhibit a seasonal pattern. Composite indices like the UTCI and the H index can be useful tools for predicting the risk of herpes zoster. The relative risk of herpes zoster is lower during cold stress conditions and higher during heat stress conditions.